Disparitas Pembangunan Wilayah Pesisir (Studi Kasus Kabupaten Pangkajene dan Kepulauan) - Hasriyanti, Hasriyanti; Rammang, Grace Amanda; Ali, Mutmainnah; Susiyanti, Susiyanti (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2023)
Coastal areas often have great economic potential because of easy access to natural resources, harbors, tourism, and trade activities. However, in many cases coastal development is uneven, and significant disparity occurs between developed regions and those left behind. The disparity of coastal development refers to significant differences in the development rate between different coastal regions. The problem of coastal development involves a few aspects to consider: development disparity: coastal regions often face disparity between those that have developed and those that have been left behind. Some coastal areas may have experienced significant economic growth and infrastructure development, while others are falling behind and lack access to basic resources and services. This study uses case studies the case study is the coastal region of kab. Pangkajene and islands. The case study method uses development inequality analysis methods. Size to analyze how high regional disparity is by means of the Williamson index (Williamson, 1965). The findings show the county of pangkajene is still below the standards of the provinces and the national. And still, inequality and inequality of people or gini ratio ratio to pangkajene and islands counties.